Effect of Installation Error on the Load Sharing Characteristic of Power Three-branching Transmission - Dong Hao; Wang Baobin; Fang Zhou; Zhao Xiaolong (Jixie chuandong)
The power three- branching transmission system is constituted by the power double- branching transmission system and planetary gear train. In order to reveal the load distribution mechanism of power three- branching transmission system,the each gear torsion angle deformation coordination conditions,moment balance condition and elastic support condition under the power flow closed- loop characteristics are established,the load sharing coefficient is obtained. The influence of the installation error,floating and torsional rigidity on the load sharing characteristic is analyzed. The results show that the installation error is the main factor affecting the load characteristics,and the larger the error,the lower the load performance. The load sharing coefficient fluctuates between 1. 04 and 0. 96 when the sun wheel and the inner ring are floating. The load distribution is within 5%,which can improve the performance of the load.